(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
As a result of advancements in technology and software, the artificial intelligence (AI) has integrated into creative industries. AI has introduced novel approaches to various aspects of dance production, including costume design, choreographic composition, and animated dance creation. As a result, dance has extended beyond the boundaries of live stage performance and has increasingly become integrated into virtual and digital platforms. The creation of dance animation is a complex and multi-layered process that involves the anthropomorphizing of non-living or virtual characters into lifelike forms. It requires the integration of full-body movement, expressive gestures, costume design, in to rhythmic cultural and traditional way to achieve a coherent and believable performance. The primary problem of this research is to determine whether human-created or AI-generated animated dance is more effective and realistic from the audience’s perspective. In addition, the study seeks to investigate the extent to which artificial intelligence influences dance animation in terms of visual quality, emotional expression, and conceptualization. This study adopts a mixed-method research design to examine audience perceptions of AI-generated and human-created animated dance. A purposive sample of fifty participants with prior knowledge of dance and media will be selected. Quantitative data collected through questionnaires and qualitative data collected from audience observation and discussions. The findings of this research AI-generated dance content enhance visual appeal and accessibility, particularly in digital and social media contexts and it may lack the depth of emotional expression typically associated with human performance. The study concludes that AI does not replace traditional dance practices but rather expands the possibilities of dance as a hybrid digital art form.